Organizational Analysis: Case of a Leading Distance Education Provider in Malaysia - Asaari, Muhammad Hasmi Abu Hassan (Globeedu Group, 2017)
This paper focuses on a case, a leading distance education provider, in Malaysia. The provider will be examined on its organizational analysis, namely its strengths and weaknesses. Moreover, the analysis will be on the number of publication produced by the provider’s lecturers in 2015 and 2016 as deliverables toward their Key Performance Indicators (KPI). The distance education provided had manpower of 76 lecturers in various programs, namely Science, Social Sciences, Arts, and Management. Positively, this paper contributes to views and suggestions in boosting the distance education provider’s 2017 KPI and views on the distance education provider’s leadership.